(3ZfjI GddHjH YfO ZjHI GdWHjHs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s ((3GdbSWfWjfI s)
(3ChdgG (B:s
(3hHYO (B: (3agPg QSGdI dWjaI GdMLe , ZRjQI GdYde JTJed Ydi eGdGHO efg s
(3BNQgG (B:s
(3hcPdc ef fXQ Edi hQO GdNWejI hgh Ydi TLQJg hOGQ Mhdg SHY OhQGJ s
(3hbO VHWJ ajgG GdGUWdMGJ HGdTcds
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B137 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B133 s
Keywords: (3GdWHs